The Perception of Judges in the Religious Court of Parepare Regarding the Increase in Marriage Age in Law Number 16 of 2019 (Jurnal Marital: Kajian Hukum Keluarga Islam, 2023)
This research aims to find out the things that are considered to increase the age limit for marriage and The social impact caused by changes in the legal age limit for marriage.This type of research is qualitative research using an empirical juridical approach, namely an approach carried out directly in the field to find out the actual problems that occur, then it will be connected to the applicable laws and regulations and the theory used. The results of this research show that: 1) there are several things that encourage and are considerations for increasing the marriage age limit in Law Number 16 of 2019, namely first, to reduce early marriage, especially for women. Second, based on the consideration of school age factors to protect children's rights from fulfilling their educational rights. Third, to protect children's rights from fulfilling reproductive health rights. Fourth, consider the age of maturity from a psychological perspective. 2) The revision of the Marriage Law has more or less had an impact on society, both positive and negative and has an impact on its implementation which is inversely proportional to the hopes and objectives of the Law.